The Effectiveness of Neroli Aromatherapy in Reducing Labor Pain Intensity During the Active Phase Among Mothers at RSUD Dr. Sayidiman Magetan - Rizki Tweniari; Tutiek Herlina; Nana Usnawati; Rahayu Sumaningsih (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2026)
Labor pain during the active phase of childbirth remains a significant clinical and psychological challenge for mothers and is often associated with increased anxiety, prolonged labor, and negative birth experiences. In many maternity settings, pain management is still limited to basic relaxation techniques, while evidence-based non-pharmacological alternatives such as aromatherapy are not routinely implemented. This study aimed to examine the effectiveness of neroli (Citrus aurantium) aromatherapy in reducing labor pain intensity during the active phase of the first stage of labor. A quasiexperimental study with a pretest–posttest control group design was conducted at RSUD dr. Sayidiman Magetan. A total of 60 laboring mothers in the active phase (cervical dilatation 4–6 cm) were recruited using consecutive sampling and equally allocated into an intervention group (neroli aromatherapy) and a control group (breathing relaxation). The intervention consisted of inhalation of neroli essential oil via an ultrasonic diffuser for 45 minutes under standardized environmental conditions. Labor pain intensity was measured before and after the intervention using the Visual Analog Scale (VAS). Data were analyzed using the Wilcoxon Signed-Rank test and the Mann–Whitney U test. The results demonstrated a significant reduction in pain intensity in the intervention group, with a mean VAS score decreasing from 6.77 to 5.43 (mean difference = 1.33; p < 0.001). In contrast, the control group experienced a slight increase in pain intensity, with mean scores rising from 6.57 to 6.97 (mean difference = +0.40; p = 0.005). Post-intervention comparisons between groups showed a statistically significant difference (p < 0.001), indicating superior pain reduction in the aromatherapy group. In conclusion, neroli aromatherapy is an effective, safe, and non-pharmacological intervention for reducing labor pain during the active phase of childbirth. Its integration into routine midwifery care may enhance maternal comfort and support a more positive labor experience.